REVALIDATION OF LEARNERS’ LEARNING ENGAGEMENT SCALE IN ONLINE ESL CLASSROOM: A FUZZY DELPHI APPROACH - Zuriani Yaacob; Pauline Georgina Priya Hebert Sundram; Khamizatul Baizura Idris; Faiza Rostam Affendi (Journal of Islamic, Social, Economics and Development, 2023)
To measure the success of English as a second language (ESL) acquisition, second language (L2) learners must consistently utilise integrated language skills in their learning process. Online language learning classrooms are proliferating, necessitating L2 learners' proactive participation in the online engagement scenario. In this context, investigations on learners' perceptions of their online L2 involvement must be prioritised in order to address any connected concerns, to identify issues and their causes, and so on. Thus, this study presented a new input that indicated items that suited the standards by using the Fuzzy Delphi approach to revalidate the questionnaire items on the subject matter based on expert consensus. Finally, it is recommended to conduct further research utilising a mixed method so that the data gathered is more comprehensive, as well as to gather experts from various affiliations for their opinions and agreement.